Processing method for improving imaging quality of cemented prism and bonded prism

By using patterned film layers and room-temperature bonding technology for bonded prisms, the problem of image quality degradation caused by pits in cemented prisms has been solved, achieving efficient and low-cost optical performance improvement.

CN119270400APending Publication Date: 2025-01-07HANGZHOU MDK OPTO ELECTRONICS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411510498.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing cemented prisms suffer from pits on the sides of the cemented layer due to the difference in thermal expansion and contraction between the optical adhesive and the optical lens materials during the imaging process. This causes scattering, diffraction and reflection, affecting the image quality. Furthermore, the traditional filling and polishing process is complex and costly.

Method used

By replacing adhesive bonding with bonding, patterned film processing and bonding layer coating are performed on the surface of the optical lens, combined with room temperature bonding technology, to ensure a smooth and seamless lens surface. This is achieved through a reasonable structural design and a simplified processing procedure.

Benefits of technology

It significantly improves imaging quality, simplifies the processing flow, reduces production costs, solves the stray light problem caused by pits in cemented prisms, increases the optical working area, and improves optical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119270400A_ABST
    Figure CN119270400A_ABST
Patent Text Reader

Abstract

The invention provides a processing method for improving the imaging quality of a cemented prism and a bonded prism, and the method comprises the steps: (1) carrying out the graphical film processing of one side of a first optical lens, and enabling the thickness of a film to be 0.5-2 microns; (2) carrying out bonding layer processing on the first optical lens and / or the second optical lens to ensure that the thickness of the bonding layer is more than 1 [mu] m greater than the thickness of the graphical film layer, then polishing, and controlling the height difference between the film layer thickness of the bonding layer of the first optical lens and the graphical film layer to be less than 200nm and the film layer thickness of the bonding layer of the second optical lens to be 10nm-1000nm; and (3) bonding the first optical lens and the second optical lens at room temperature under the conditions that the vacuum degree is higher than 6 * 10 <-6 > Pa and the room temperature is reached. According to the invention, the two optical lenses are directly fixed together by adopting a normal-temperature glue-free bonding process, the prism obtained by the process does not have a pit at the joint, the phenomenon of stray light caused by the pit is solved, and the imaging quality is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optical element processing, and in particular to a processing method for improving the degradation of imaging quality of a glued prism caused by stray light during the imaging process, and in particular to a processing method for improving the imaging quality of a glued prism and a bonded prism. Background Art

[0002] As an important optical element, cemented prisms are widely used in various optical devices and systems to achieve complex optical functions and precise optical operations. Usually, two or more prisms are glued together with specific glue or adhesive materials. However, in the prior art, during the preparation of cemented prisms, due to the difference in thermal expansion and contraction between the optical glue and the optical lens material, pits are often generated on the side of the cementing layer, which in turn causes scattering, diffraction and reflection during the imaging process, seriously affecting the imaging quality. In order to overcome this problem, traditional methods often use complex and costly side multiple coating, filling and polishing processes, but the effect is not significant. In addition, due to the difference in refractive index between the coating material of the filling layer and the glue, the available working area on the surface of the optical lens will also be affected. Summary of the invention

[0003] In order to overcome the problems in the prior art, the present invention discloses a processing method for improving the imaging quality of a bonded prism, aiming to provide a bonding prism processing method with reasonable structural design, simplified processing flow and low cost. The method adopts a bonding method instead of a gluing method, thereby improving the prism bonding effect while ensuring the optical performance of the prism.

[0004] To achieve the above object, the present invention provides a processing method for improving the imaging quality of a cemented prism, which comprises the following steps:

[0005] (1) Processing a patterned film layer on one side of the first optical lens, wherein the film layer thickness is 0.5 to 2 μm;

[0006] (2) The bonding layer of the first optical lens and / or the second optical lens is processed and polished. The height difference between the film thickness of the bonding layer of the first optical lens and the patterned film layer is controlled to be less than 200nm, and the film thickness of the bonding layer of the second optical lens is 10 to 1000nm. After polishing, the surface roughness of the first optical lens and the second optical lens is Ra < 0.5nm, TTV is less than 3um, and PV ≤ 25um;

[0007] (3) When the vacuum degree is higher than 6×10 -6 Pa, and bond the first optical lens and the second optical lens at room temperature.

[0008] Preferably, before the bonding layer is processed in step (1), the surfaces of the first optical lens and the second optical lens need to be pretreated to a surface roughness of Ra < 0.5 nm, TTV less than 3 um, and PV ≤ 25 um.

[0009] Preferably, in step (2), the bonding layer is processed by coating the bonding layer on the bonding interface of the first optical lens and / or the second optical lens, and the absolute value of the difference between the refractive index of the coating material of the bonding layer and the refractive index of the first optical lens and / or the second optical lens is maintained within 0.3.

[0010] Preferably, the coating material of the bonding layer includes one or more of Al, Al2O3, Si, SiO2, Ti, TiO2, and Ti2O3.

[0011] Preferably, in step (3), the surface of the optical lens is activated by an ion beam before the room temperature bonding.

[0012] Preferably, after step (3), the prism obtained by bonding is subjected to one or more of wire cutting processing, shape and surface processing, silk screen processing, and slitting processing as needed.

[0013] Preferably, the screen printing uses low-reflective ink with a thickness of 2 to 10 um, and the average reflectivity of the ink in the 400 to 700 nm band is less than 0.3%, and the maximum reflectivity is less than 0.5%.

[0014] The present invention also provides a bonded prism, which includes a first optical lens and a second optical lens, a patterned film layer is arranged on the first optical lens, and the first optical lens and the second optical lens are fixed as a whole through the bonding layer.

[0015] Preferably, the material of the first optical lens includes one or more of BSL-7 and H-BaF6; the material of the second optical lens includes one or more of BSL-7 and H-BaF6; the material of the patterned film layer includes one or more of SiO2, TiO2, Ti, and Nb2O5; the material of the bonding layer includes one or more of Al, Al2O3, Si, SiO2, Ti, TiO2, and Ti2O3.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The present invention uses a room temperature glue-free bonding process to directly fix two optical lenses together. The prism obtained by this process does not have the problem of pits at the joint, which solves the problem of stray light caused by pits. The improvement effects are as follows:

[0018] 1. Significantly improved imaging quality: The present invention bonds two optical lenses together through a glue-free room temperature bonding process, solving the problem of pits in the side bonding area caused by the glue bonding process. The atomic force microscope measurement results show that the two optical lenses are directly bonded together through the room temperature bonding process, and there are no gaps in the bonding layer and no pits on the sides. The entire side is level on a plane, which solves the scattering, diffraction and reflection phenomena caused by pits, and significantly improves the imaging quality. Compared with the prior art, the side coating and polishing technology is used to solve the problem of optical path deviation caused by uneven and inconsistent refractive indices of glue and coating layers, so that the incident light forms total reflection in the bonding layer of the prism, and the incident light of the first optical lens is totally reflected to the second optical lens when it reaches the bonding area, thereby increasing the optical action area of ​​the prism.

[0019] 2. Simplified processing flow: Compared with the traditional process of multiple side coating, filling and polishing, the processing flow of the present invention is simpler and faster, which significantly reduces the production cost.

[0020] 3. Reasonable structural design: The reasonable silk-screen layer thickness and reflectivity design of the present invention make the overall optical performance of the prism more superior.

[0021] 4. Wide range of applications: The present invention can be applied to various optical devices and systems that require high-precision imaging, such as telescopes, microscopes, cameras, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The optical path diagram of the bonded prism of the present invention;

[0023] Figure 2 It is a schematic diagram of the structure of a glued coated prism in the prior art;

[0024] Figure 3 A schematic diagram of removing the coating layer from a prior art glued coated prism;

[0025] Figure 4 is a schematic structural diagram of a prism in Example 1 of the present invention;

[0026] Figure 5 This is the morphology of the pits on the side of the bonding layer in the prism bonding process. The pits can be clearly seen, and the depth of the pits is 529nm;

[0027] Figure 6 From the side morphology diagram of the bonding layer of the bonding process in the first embodiment, it can be clearly seen that there are no pits.

[0028] Figure 7 From the side morphology diagram of the bonding layer of the bonding process in the second embodiment, it can be clearly seen that there are no pits. DETAILED DESCRIPTION

[0029] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present application will be further described below in conjunction with specific embodiments.

[0030] The technical solution adopted by the present invention is: a method for processing a bonded prism, wherein the bonded prism comprises:

[0031] A first optical lens;

[0032] A second optical lens;

[0033] A patterned film layer is coated on the surface of the first optical lens;

[0034] A bonding layer, through which the first optical lens and the second optical lens are fixed as a whole;

[0035] Configure the first optical lens and the second optical lens, and connect the first optical lens and the second optical lens through the bonding layer.

[0036] The process for preparing bonded prisms is as follows:

[0037] 1. Optical lens processing: Select suitable transparent materials such as optical glass or quartz as the first optical lens and the second optical lens, perform wire cutting, grinding and polishing on the first and second optical lenses, and the surface roughness of the polished lenses should be Ra<0.5nm, TTV≤3um, and PV≤25um (Ra here refers to the surface roughness of the optical lens, TTV refers to the total dispersion of the optical lens thickness, and PV value refers to the difference between the highest and lowest points on the optical lens surface);

[0038] 2. Patterned film processing: one side of the first optical lens is subjected to glue coating, exposure, development, coating, degumming, and ultrasonic cleaning to achieve patterned film processing with a film thickness of 0.5 to 2 um;

[0039] 3. Bonding layer processing: the bonding layer is processed on the surface of the patterned first optical lens, the film thickness of the bonding layer on the surface of the first optical lens is more than 1um higher than the thickness of the patterned film layer, and the bonding layer is processed on the surface of the second optical lens, and the bonding layer thickness is 10 to 1000nm;

[0040] 4. Polishing: Polish and level the first optical lens processed by the bonding layer. After polishing, the height difference between the film thickness of the bonding layer and the patterned film layer is controlled below 200nm, the surface roughness of the film layer is less than 0.5nm, the TTV is less than 3um, and the PV is ≤25um;

[0041] 5. Room temperature bonding: Bond the flattened first optical lens and the second optical lens at room temperature. First, perform ultrasonic cleaning on the first and second optical lenses to remove foreign matter on the surface, and then use Ar ion beam to activate the surface to remove the surface oxide layer and pollutants, making the surface highly active. Put the activated wafer surface in close contact, and apply pressure to the product under ultra-high vacuum, with a vacuum degree higher than 6*10^-6Pa. At room temperature, the surface energy is reduced by the action of chemical bonds, achieving a strong bond at the atomic scale.

[0042] 7. Wire cutting: The bonded large optical lenses are wire cut to cut into strip prisms of the required shape;

[0043] 8. Shape and surface processing: Shape the strip prism into the required shape, and finely grind and polish the prism to ensure surface smoothness and flatness;

[0044] 9. Silk screen printing: The prism is silk screened and then heat cured in a dust-free oven at a baking temperature of 150-200°C for 30-60 minutes. The silk screen layer uses a specific low-reflective ink with a thickness of 2-10um. The average reflectivity of the ink in the 400-700nm band is less than 0.3%, and the maximum reflectivity is less than 0.5%.

[0045] 10. Cutting: Cut the strip prism into the final required prism;

[0046] The absolute value of the difference between the refractive index of the coating material of the bonding layer and the refractive index of the optical substrate in the embodiment of the present invention is maintained within 0.3 to reduce the optical impact caused by the refractive index difference.

[0047] In the polishing process described in the embodiment of the present invention, the height difference between the film thickness of the bonding layer and the patterned film layer after polishing is controlled to be less than 200nm, the surface roughness of the film layer is less than 0.5nm, the TTV is less than 3um, and the PV is ≤25um;

[0048] The screen printing ink reflectivity of the embodiment of the present invention has an average reflectivity of less than 0.3% in the 400-700nm band and a maximum reflectivity of less than 0.5%;

[0049] In the embodiment of the present invention, the materials of the first optical lens and the second optical lens are the same or different.

[0050] Example 1

[0051] In this embodiment, the first optical lens is H-BaF6 with a refractive index of 1.61, the second optical lens is H-BaF6 with a refractive index of 1.61, the patterned film layer is a low-reflection, low-transmittance black film, and the coating is on the surface of the first optical lens; the bonding layer is AL2O3 with a refractive index of 1.62.

[0052] The process for preparing bonded prisms is as follows:

[0053] 1. Optical lens processing: Select suitable transparent materials such as optical glass or quartz as the first optical lens and the second optical lens, perform wire cutting, grinding and polishing on the first and second optical lenses, and the surface roughness of the polished lenses should be Ra<0.5nm, TTV≤3um, and PV≤25um (Ra here refers to the surface roughness of the optical lens, TTV refers to the total dispersion of the optical lens thickness, and PV value refers to the difference between the highest and lowest points on the optical lens surface);

[0054] 2. Graphical film processing: one side of the first optical lens is subjected to gluing, exposure, development, coating, degumming, and ultrasonic cleaning to achieve graphic black film processing with a film thickness of 0.7um;

[0055] 3. Bonding layer processing: The bonding layer is processed on the surface of the patterned first optical lens by evaporation or sputtering coating. The bonding layer material is Al2O3 with a thickness of 2um. The bonding layer is processed on the surface of the second optical lens by evaporation or sputtering coating. The bonding layer material is Al2O3 with a bonding layer thickness of 20nm.

[0056] 4. Polishing: Polish and level the first optical lens processed by the bonding layer. After polishing, the bonding surface is in a horizontal state, the surface roughness is less than 0.5nm, the TTV is less than 3um, and the PV is 10um. After polishing, the thickness of the bonding layer above the graphic black film is 50nm;

[0057] 5. Room temperature bonding: The first optical lens and the second optical lens after flattening are bonded at room temperature. First, the first and second optical lenses are ultrasonically cleaned to remove foreign matter on the surface. Then, the product surface is activated with Ar ion beam. The Ar flow rate is 250cfm, the power is 300w, and the activation time is 200s to remove the surface oxide layer and pollutants, making the surface highly active. The activated wafer surfaces are closely contacted and pressure is applied to the product under ultra-high vacuum. The vacuum degree is 8×10 -6 6Pa, at room temperature, relying on the effect of chemical bonds, the surface energy is reduced, achieving a strong bond at the atomic scale to form an Al-O-Al bond;

[0058] 7. Wire cutting: The bonded large optical lenses are wire cut to cut into strip prisms of the required shape;

[0059] 8. Shape and surface processing: Shape the strip prism into the required shape, and finely grind and polish the prism to ensure surface smoothness and flatness;

[0060] 9. Silk screen printing: The prism is silk screened and then heat cured in a dust-free oven at a baking temperature of 150°C for 60 minutes. The ink thickness of the silk screen layer is 8um. The average reflectivity of the ink in the 400-700nm band is 0.15%, and the maximum reflectivity is 0.4%.

[0061] 10. Cutting: Cut the strip prism into the final required prism;

[0062] The absolute value of the difference between the refractive index of the coating material of the bonding layer and the refractive index of the optical substrate in the embodiment of the present invention is maintained within 0.3 to reduce the optical impact caused by the refractive index difference.

[0063] In the polishing process described in the embodiment of the present invention, the height difference between the film thickness of the bonding layer and the patterned film layer after polishing is controlled to be less than 200nm, the surface roughness of the film layer is less than 0.5nm, the TTV is less than 3um, and the PV is ≤25um;

[0064] The reflectivity of the screen printing ink in the embodiment of the present invention is less than 0.3% on average in the 400-700nm band, and less than 0.5% at maximum. As shown in the atomic force microscope test diagram, the prism processed by the gluing process has a pit of about 500nm at the side gluing, and the glue thickness is about 3um; while the prism processed by the room temperature bonding process has no bonding gap and pit phenomenon at the side atomic force microscope observation point.

[0065] Example 2

[0066] In this embodiment, the first optical lens is BSL-7 with a refractive index of 1.51, the second optical lens is BSL-7 with a refractive index of 1.51, the patterned film layer is a low-reflection, low-transmittance black film, and the coating is on the surface of the first optical lens; the bonding layer is SiO2 with a refractive index of 1.49.

[0067] The process for preparing bonded prisms is as follows:

[0068] 1. Optical lens processing: Select suitable transparent materials such as optical glass or quartz as the first optical lens and the second optical lens, perform wire cutting, grinding and polishing on the first and second optical lenses, and the surface roughness of the polished lenses should be Ra < 0.5nm, TTV less than 3um, and PV less than 25um (Ra here refers to the surface roughness of the optical lens, TTV refers to the total dispersion of the thickness of the optical lens, and PV value refers to the difference between the highest and lowest points on the surface of the optical lens);

[0069] 2. Graphical film processing: one side of the first optical lens is subjected to gluing, exposure, development, coating, degumming, and ultrasonic cleaning to achieve graphic black film processing with a film thickness of 1.5um;

[0070] 3. Bonding layer processing: The bonding layer is processed on the surface of the patterned first optical lens by evaporation or sputtering coating. The bonding layer material is SiO2 with a thickness of 4um. The bonding layer is processed on the surface of the second optical lens by evaporation or sputtering coating. The bonding layer material is SiO2 with a thickness of 50nm.

[0071] 4. Polishing: Polish and level the first optical lens processed by the bonding layer. After polishing, the bonding surface is in a horizontal state, the surface roughness is less than 0.5nm, TTV is less than 3um, PV≤20um, and the thickness of the bonding layer above the graphic black film is 100nm after polishing;

[0072] 5. Room temperature bonding: The first optical lens and the second optical lens after flattening are bonded at room temperature. First, the first and second optical lenses are ultrasonically cleaned to remove foreign matter on the surface. Then, the product surface is activated with Ar ion beam. The Ar flow rate is 250cfm, the power is 300w, and the activation time is 300s to remove the surface oxide layer and pollutants, making the surface highly active. The activated wafer surface is closely contacted and pressure is applied to the product under ultra-high vacuum. The vacuum degree is 12×10 -6 Pa, at room temperature, relies on the action of chemical bonds to reduce the surface energy, achieve strong bonding at the atomic scale, and form Si-O-Si bonds;

[0073] 7. Wire cutting: The bonded large optical lenses are wire cut to cut into strip prisms of the required shape;

[0074] 8. Shape and surface processing: Shape the strip prism into the required shape, and finely grind and polish the prism to ensure surface smoothness and flatness;

[0075] 9. Silk screen printing: The prism is silk screened and then heat cured in a dust-free oven at a baking temperature of 200°C for 30 minutes. The ink thickness of the silk screen layer is 8um. The average reflectivity of the ink in the 400-700nm band is 0.15%, and the maximum reflectivity is 0.4%.

[0076] 10. Cutting: Cut the strip prism into the final required prism;

[0077] The absolute value of the difference between the refractive index of the coating material of the bonding layer and the refractive index of the optical substrate in the embodiment of the present invention is maintained within 0.3 to reduce the optical impact caused by the refractive index difference.

[0078] In the polishing process described in the embodiment of the present invention, the height difference between the film thickness of the bonding layer and the patterned film layer after polishing is controlled to be less than 200nm, the surface roughness of the film layer is less than 0.5nm, the TTV is less than 3um, and the PV is ≤25um;

[0079] The reflectivity of the screen printing ink in the embodiment of the present invention is less than 0.3% on average in the 400-700nm band, and less than 0.5% at maximum. As shown in the atomic force microscope test diagram, the prism processed by the gluing process has a pit of about 500nm at the side gluing, and the glue thickness is about 3um; while the prism processed by the room temperature bonding process has no bonding gap and pit phenomenon at the side atomic force microscope observation point.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A processing method for improving the imaging quality of a cemented prism, characterized in that: The following steps are included: (1) Processing a patterned film layer on one side of the first optical lens, wherein the film layer thickness is 0.5 to 2 μm; (2) Processing the bonding layer of the first optical lens and / or the second optical lens to ensure that the thickness of the bonding layer is more than 1 um higher than the thickness of the patterned film layer, and then polishing. The height difference between the film thickness of the bonding layer of the first optical lens and the patterned film layer is controlled to be less than 200 nm, and the film thickness of the bonding layer of the second optical lens is 10 to 1000 nm. After polishing, the surface roughness of the first optical lens and the second optical lens is Ra < 0.5 nm, TTV is less than 3 um, and PV ≤ 25 um; (3) When the vacuum degree is higher than 6×10 -6 Pa, and bond the first optical lens and the second optical lens at room temperature.

2. The method for improving the imaging quality of a cemented prism according to claim 1, characterized in that: Before performing patterned film processing in step (1), the surfaces of the first optical lens and the second optical lens need to be pre-treated to a surface roughness of Ra < 0.5 nm, TTV less than 3 um, and PV ≤ 25 um.

3. The method for improving the imaging quality of a cemented prism according to claim 1, characterized in that: In step (2), the bonding layer is processed by coating the bonding layer on the bonding interface of the first optical lens and / or the second optical lens, and the absolute value of the difference between the refractive index of the coating material of the bonding layer and the refractive index of the first optical lens and / or the second optical lens is maintained within 0.

3.

4. The method for improving the imaging quality of a cemented prism according to claim 1, characterized in that: The coating material of the bonding layer includes one or more of Al, Al2O3, Si, SiO2, Ti, TiO2, and Ti2O3.

5. The method for improving the imaging quality of a cemented prism according to claim 1, characterized in that: In step (3), the surface of the optical lens is activated by an ion beam before the room temperature bonding.

6. The method for improving the imaging quality of a cemented prism according to claim 1, characterized in that: After step (3), the bonded prism is subjected to one or more of wire cutting, shape and surface processing, silk screen processing, and slitting processing as required.

7. The method for improving the imaging quality of a cemented prism according to claim 5, characterized in that: The silk-screen processing uses low-reflection ink with a thickness of 2-10 μm, and the average reflectivity of the ink in the 400-700 nm waveband is less than 0.3%, and the maximum reflectivity is less than 0.5%.

8. A bonded prism, characterized in that: It comprises a first optical lens and a second optical lens, wherein a patterned film layer is arranged on the first optical lens, and the first optical lens and the second optical lens are integrated into one through the bonding layer.

9. The prism according to claim 8, characterized in that: The material of the first optical lens includes one or more of BSL-7 and H-BaF6; the material of the second optical lens includes one or more of BSL-7 and H-BaF6; the material of the patterned film layer includes one or more of SiO2, TiO2, Ti, and Nb2O5; the material of the bonding layer includes one or more of Al, Al2O3, Si, SiO2, Ti, TiO2, and Ti2O3.

Citation Information

Cited By

  • Processing method for improving imaging quality of cemented prism and cemented prism

    CN120972340A